2014
DOI: 10.1371/journal.pone.0107418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Low Level Laser Therapy on Oral Mucositis: A Systematic Review and Meta-Analysis

Abstract: BackgroundObjective was to determine whether prophylactic low level laser therapy (LLLT) reduces the risk of severe mucositis as compared to placebo or no therapy.MethodsMEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials were searched until February 2014 for randomized controlled trials (RCTs) comparing prophylactic LLLT with placebo or no therapy in patients with cancer or undergoing hematopoietic stem cell transplantation (HSCT). All analyses used random effects models.ResultsEighteen RCTs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 48 publications
2
80
0
23
Order By: Relevance
“…LLLT in the supportive care of breast cancer patients Different clinical trials investigated the use of LLLT for a variety of side effects related to breast cancer treatment, such as breast cancer-related lymphedema (BCRL), oral mucositis (OM), radiodermatitis (RD), chemotherapy-induced peripheral neuropathy (CIPN), and osteonecrosis of the jaw (ONJ) [24][25][26].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelmentioning
confidence: 99%
“…LLLT in the supportive care of breast cancer patients Different clinical trials investigated the use of LLLT for a variety of side effects related to breast cancer treatment, such as breast cancer-related lymphedema (BCRL), oral mucositis (OM), radiodermatitis (RD), chemotherapy-induced peripheral neuropathy (CIPN), and osteonecrosis of the jaw (ONJ) [24][25][26].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelmentioning
confidence: 99%
“…In case of irradiation of tumours of the head and neck this complication is the most intensified in 4-6 weeks after treatment and usually lasts for a few weeks after radiotherapy [24].…”
Section: Streszczeniementioning
confidence: 99%
“…Thus, it was concluded that prophylactic LLLT helped in reducing severe mucositis and pain in patients with cancer and HSCT recipients. [17] It is recommended to have a 780-830 (nm) (infrared) Wavelength for analgesia with output between 10 and 100 (mW) which could be fixed or variable depending on the equipment and dose of 0.08-2 (J). [18] …”
Section: Mucositis Painmentioning
confidence: 99%